‘CONSUMMATUM EST’: CALVINIST EXEGESIS, MIMESIS AND DOCTOR FAUSTUS - Streete, Adrian (Literature and theology, 2001)
In this article, I examine the connections between Christopher Marlowe’s Doctor Faustus and sixteenth century Calvinist Christology. Focusing on the magician's response to various New Testament texts as well as his relationship to Mephistopheles, I argue that by replicating Faustus’ appeal to utter subjectiveness in all that he does, many critics have neglected to consider the way in which relationality is dealt with both in early modern Calvinism and in the play By concentrating on the Calvinist conception of Christ as a masochistic paradigm of selfhood, the play offers a comment on the violence that underwrites this form of Calvinist subjectivity. But more than this, it also provides an analysis of a culture grappling with a radical shift in affective response to the saviour.